Strategi Keberlanjutan Program Usaha Mikro, Kecil, dan Menengah (UMKM) melalui Permberdayaan Narapidana di Lapas Kelas I Malang dan Lapas Kelas I Surabaya - Brilliano Kevin Bayu Aviary; Irvan Sebastian Iskandar (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This study aims to analyze the sustainability strategies of Micro, Small, and Medium Enterprises (MSMEs) programs through inmate empowerment at Class I Correctional Institutions in Malang and Surabaya. The MSME program is positioned not only as a form of self-reliance training but also as a means of social and economic rehabilitation for inmates. The research employs a qualitative case study approach with data collected through observation, in-depth interviews, and documentation. The study applies the Triple Bottom Line theory (profit, people, planet) by Elkington and Porter's competitive advantage theory as analytical frameworks. The findings indicate that each institution applies unique sustainability strategies with distinct advantages and limitations. Lapas Malang emphasizes agriculture-based production but faces challenges in market access and technology. In contrast, Lapas Surabaya benefits from industrial partnerships, yet heavily relies on a single partner. The implementation of sustainability strategies—covering economic, social, and environmental dimensions—shows varying degrees of effectiveness depending on structural support and stakeholder involvement. The study concludes that MSME sustainability in correctional settings requires integrated multidimensional strategies, long-term partnerships, and inmate empowerment aligned with socio-economic developments.